Reduction of current collapse in AlGaN/GaN MISHEMT with bilayer SiN/Al2O3 dielectric gate stack - Anand, M. J. (2014)
We have studied the drain current dispersion characteristics of conventional AlGaN/GaN HEMTs and SiN/Al2O3/AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors (MISHEMT) fabricated on silicon substrate. The fabricated MISHEMT exhibited an IDmaxof >1000 mA/mm and gmmax of 241 mS/mm. Compared to conventional AlGaN/GaN HEMTs, about an order of magnitude lower gate leakage current and a ∼ 60% reduction in drain current (ID) collapse was observed in the MISHEMTs. The observation of low ID collapse is due to the occurrence of low interface state density (6.39 × 1010 eV-1 cm-2) between the bilayer dielectric (SiN/Al2O3) and GaN surface which is confirmed through the AC-conductance method.